Development of Integrated Thematic Educational Teaching Materials Based on Contextual Teaching Learning to Increase Self Efficacy - Anna Mariyani; Husna Imro’athush Sholihah; Mia Andini Nurfita (Nur Science Institute, 2025)
Background: Contextual-based teaching materials are able to bring the real world into the classroom and encourage students to make connections between the knowledge they have and its application in real life. Method: This research is research and development because it produces a product in the form of contextual-based thematic teaching materials. The development model used is Borg & Gall (1983). According to Borg & Gall, research and development is a process to develop and validate the developed product. Result: The results of this study showed that the material expert validated once, this was due to the average score of the material validation results showing a value of 3.61 which is included in the good category so that the interactive learning media has met the standards for testing. The media expert validated twice. This was due to the average score of the media expert validation results in stage I still showing a value of 3.35 which is included in the sufficient category so that it has not met the standards for testing. Validation by the media expert in stage II showed an average score of 3.7 which is included in the good category. Based on these results, the media is suitable for testing. The material expert validated once the average score was 3.61 with the